Systematic orientation of fresh rectal suction biopsies improves histopathological diagnostics in hirschsprung's disease - a method description and preliminary report - Emma Fransson; Emilia Gottberg; Rodrigo Munoz Mitev; David Gisselsson; Kristine Hagelsteen; Louise Tofft; Pernilla Stenström; Christina Granéli (BMC, 2023)
Abstract Background Optimizing rectal suction biopsy (RSB) diagnostics in Hirschsprung's disease (HD) may shorten diagnostic time and prevent need for repeated biopsies. Aim To explore whether systematic orientation of fresh RSB specimens increased biopsy quality, diagnostic times, diagnostic efficacy, and histopathologic workload, and to explore these outcome measures for aganglionic specimens. Materials/Methods This was an observational case-control study conducted at a national referral center for HD on data collected from the local HD-diagnostic register. From 2019 each fresh RSB was oriented by the collector in a notch in a foam cushion, placed in a separate cassette, and sent in formalin for pathological analysis. Outcome measures of oriented RSB samples collected 2019-2021 were compared to those of non-oriented RSB samples collected 2015-2018. Staining/immunohistochemistry consisted of hematoxylin eosin, S-100 and calretinin. Results 78 children with 81 RSBs and 242 biopsy analyzes were included. The frequency of high-quality RSB specimens was higher in oriented: 40% (42/106) versus non-oriented 25% (34/136) (p = 0.018), the diagnostic turnaround time was shorter: 2 days (1-5) versus 3 days (2-8) (p = 0.015), and the number of additional sectioning/leveling/re-orientation per biopsy was lower: 7 (3-26) versus 16 (7-72) (p = 0.011). Specifically for aganglionic specimens, the frequency of high-quality biopsies was generally higher in oriented than in non-oriented RSB specimens: 47% (28/59) versus 14% (7/50) (p < 0.001); the diagnostic efficacy was higher 95% (19/20) versus 60% (9/15) (p = 0.027) and the diagnostic turnaround time shorter: 2 days (2-3) versus 3 days (2-8) (p = 0.036). Conclusions Systematic orientation of fresh RSB specimens improves HD diagnostics. Improvement was consistent in aganglionic specimens.